RELATIONSHIP BETWEEN DIGITAL MINDSET TOWARDS INDUSTRY 4.0 READINESS AND ASSESSMENT OF INDUSTRY 4.0 READINESS IN BANK BNI MAJALAYA - Parapat, Ursula Diantika; Hendarman, Achmad Fajar (Journal of Business and Management, 2021)
The Industrial Revolution is evolving again into the fourth industrial revolution known as Industry 4.0 where in this stage there is a combination between communication of technology, processor, software, sensor, to create information and value for the current manufacturing processes; hence, the style of thinking of the employees have to be relevant with the required kills to keep up with system modification. To face the advancement of industry 4.0, human resource such as digital mindset are essential. Current and future workforces that involved new environment and challenge require not only digital skill sets but also a digital mindset to ensure effective use of existing and emerging technology and information systems. As a company that has vision to become a financial institution that excels in services and performance in a sustainable manner, Bank BNI, which is a state-owned bank (BUMN) that established in 1946, definitely needs to keep improving the human resource’s quality to be able to serve relevantly with the current condition. This research aims to identify the readiness of Industry 4.0 in Bank BNI Majalaya employees and to identify the relationship between Digital Mindset and Industry 4.0 readinessKeywords: Industry 4.0 Readiness, Human Capital Readiness, Digital Mindset